International Society of Sports Nutrition position stand: meal frequency - Stout Jeffrey R; Kreider Richard B; Kleiner Susan M; Berardi John; Galvan Elfego; Wilson Jacob; Campbell Bill I; La Bounty Paul M; Ziegenfuss Tim; Spano Marie; Smith Abbie; Antonio Jose (Taylor & Francis Group, 2011)
Abstract Position Statement: Admittedly, research to date examining the physiological effects of meal frequency in humans is somewhat limited. More specifically, data that has specifically examined the impact of meal frequency on body composition, training adaptations, and performance in physically active individuals and athletes is scant. Until more research is available in the physically active and athletic populations, definitive conclusions cannot be made. However, within the confines of the current scientific literature, we assert that: 1. Increasing meal frequency does not appear to favorably change body composition in sedentary populations. 2. If protein levels are adequate, increasing meal frequency during periods of hypoenergetic dieting may preserve lean body mass in athletic populations. 3. Increased meal frequency appears to have a positive effect on various blood markers of health, particularly LDL cholesterol, total cholesterol, and insulin. 4. Increased meal frequency does not appear to significantly enhance diet induced thermogenesis, total energy expenditure or resting metabolic rate. 5. Increasing meal frequency appears to help decrease hunger and improve appetite control. The following literature review has been prepared by the authors in support of the aforementioned position statement.